Sustained-Release Powders Based on Polymer Particles for Pulmonary Delivery of Beclomethasone Dipropionate in the Treatment of Lung Inflammation - Emanuela Fabiola Craparo; Salvatore Emanuele Drago; Gabriella Costabile; Maria Ferraro; Elisabetta Pace; Roberto Scaffaro; Francesca Ungaro; Gennara Cavallaro (MDPI AG, 2023)
Inhaled corticosteroids are the mainstay in the management of lung inflammation associated to chronic lung diseases, such as asthma and chronic obstructive pulmonary disease (COPD). Nonetheless, available inhalation products are mostly short-acting formulations that require frequent administrations and do not always produce the desired anti-inflammatory effects. In this work, the production of inhalable beclomethasone dipropionate (BDP) dry powders based on polymeric particles was attempted. As starting material, the PHEA-g-RhB-g-PLA-g-PEG copolymer was chosen, obtained by grafting 0.6, 2.4 and 3.0 mol%, respectively, of rhodamine (RhB), polylactic acid (PLA) and polyethylene glycol 5000 (PEG) on alpha,beta-poly(N-2-hydroxyethyl)DL-aspartamide (PHEA). The drug was loaded into the polymeric particles (MP) as an inclusion complex (CI) with hydroxypropyl-cyclodextrin (HP-β-Cyd) (at a stoichiometric ratio of 1:1) or as free form. The spray-drying (SD) process to produce MPs was optimized by keeping the polymer concentration (0.6 wt/vol%) constant in the liquid feed and by varying other parameters such as the drug concentration. The theoretical aerodynamic diameter (daer) values among the MPs are comparable and potentially suitable for inhalation, as confirmed also through evaluation of the experimental mass median aerodynamic diameter (MMADexp). BDP shows a controlled release profile from MPs that is significantly higher (more than tripled) than from Clenil®. In vitro tests on bronchial epithelial cells (16HBE) and adenocarcinomic human alveolar basal epithelial cells (A549) showed that all the MP samples (empty or drug-loaded) were highly biocompatible. None of the systems used induced apoptosis or necrosis. Moreover, the BDP loaded into the particles (BDP-Micro and CI-Micro) was more efficient than free BDP to counteract the effects of cigarette smoke and LPS on release of IL-6 and IL-8.